Hematology Toxicities in Paclitaxel-Carboplatin Cancer Regiment - Annisa Diyan Meitasari; Dian Eka Ermawati; Sholichah Rohmani; Heru Sasongko; Muhammad Fiqri Zulpadly; Diyah Tri Utami; Nindita Clourisa Amaris Susanto; Meta Kartika Untari; Ulfa Afrinurfadhilah Darojati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Chemotherapy is one of therapy for patients with cancer. Treatment carboplatin paclitaxel regimen is usually use for cervix, breast, and ovarium cancer. But the data of ADRs in hematology toxicity caused paclitaxel-carboplatin regiment is minimal, so it is required to do research. The aim of this research is can give information about the hematology toxicity, incident, severity, relationship between risk factor due incident of myelosuppression, and relationship between pre post chemotherapy due the myelosuppression. The severity ADRs use CTCAE 5.0. The ADRs were evaluated by severity, descriptive statistics, and some bivariate analysis. Anemia (66.46%) has a highest incident and followed by leukopenia (18.18%), neutropenia (13.22%), and thrombocytopenia (9.09%). Type of cancer associate with incident of anemia, leukopenia, and thrombocytopenia. The number of cycle chemotherapy use carboplatin paclitaxel regiments affects significant with the incidence of anemia. Patients who use paclitaxel-carboplatin as a regimen chemotherapy confirmed decrease in hematologic data such as hemoglobin, leukocyte, and thrombocyte.